THE EFFECT OF USING ELSA SPEAK APPLICATION FOR STUDENTS’ PRONUNCIATION AT SMK KESEHATAN OF KAPUAS RAYA SINTANG - Martom martom; Agustinus Marjun; Lailatus Sa’adah (Universitas Kapuas, 2022)
This research aims to investigate the effect of using the Elsa Speak application on students’ pronunciation of SMK Kesehatan of Kapuas Raya Sintang in the academic year 2021/2022). The design of this research used quasi-experimental research in quantitative research. The sample of this research was XI Clinical Pharmacy as the class control and XI Nursing Assistant as the class non-control. The class control was taught by using the Elsa Speak application and class non-control was taught without using the Elsa Speak application. This selection based on purposive sampling technique. The researcher gave test in the form of pre-test and post-test to the control and non-control classes. The result of this research indicated that the Elsa Speak application was significant in improving students’ pronunciation. This was proven by the average score before treatment was 46.03 and the average score after treatment has given was 76.46. It means that using the Elsa Speak application showed a positive effect size. It was 0.58, the criteria were Moderate Effect to be implemented for students, especially for the eleventh-grade students of SMK Kesehatan of Kapuas Raya Sintang.